ETHNIC MINORITY CRISIS IN AFRICA CASE STUDY (ANGLOPHONE PROBLEM IN CAMEROON) SOCIO-ECONOMIC DEVELOPMENT - Atanga Nixon Chi (Graduate School of International Studies Ajou University, 2014)
Many minority group conflicts and marginalization has been a challenge to the peaceful existence and development of many African countries. This research work is based on the topic: Ethnic Minority crisis in Africa, with case study that of The Anglophone problem in Cameroon and specifically looking at the socio-economic development. The former British Southern Cameroonians known as Anglophones claim they are been marginalized by the Francophone’s who are the majority and ruling group. They claim that they are not politically represented both in government and decision making of the country and their regions, the North West and South West regions lag behind both in social and economic development mindful of the rich natural resources. This has created a sense of secessionist ideology. Attention is also focused on what the Anglophone movements like Southern Cameroons National Council (SCNC), All Anglophone Council (AAC), and Southern Cameroon Youth League (SCYL) have been doing to eradicate this marginalization syndrome of Anglophones and response of the Cameroonian government to provide a solution to the crisis.
학위논문(석사)--아주대학교 국제대학원 :국제개발협력과,2014. 2